THE IMPLICATIONS OF ROAD CONDITION ON ROAD USERS AND LOCAL COMMUNITIES IN INDUSTRIAL AREAS - Soerjatmodjo, Irnanda Satya; Rahayu, Tanjung; Al Kautsar, Muhammad Gibran (International Journal of Civil Engineering and Infrastructure, 2024)
The accelerated growth of the industrial sector demand reliable transportation infrastructure to facilitate the efficient circulation of commodities and economic progress. The road network in industrial zones is a critical infrastructure that serves as a strategic route essential for supporting surrounding industrial activity. Nonetheless, road damage, including cracks, deformations, and potholes, presents considerable issues by diminishing road capacity to support traffic loads and hastening pavement degradation. The road damage adversely affects both road users and the populations residing nearby. This study analyzes the impact of road deterioration on road users and adjacent communities. The results indicate that road damage substantially affects these groups, with average interpretation ratings of 4.05 for road users and 4.12 for adjacent communities, both classified as "good" in the assessment. These results highlight the necessity for efficient road repair and management to ensure the sustainability of industrial operations and community well-being.